(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: intracranial surgery is very commonly performed around the world. During these surgeries, intraoperative injury to the major intracranial vessels is a very serious condition. It has to be addressed promptly by either direct repair or vascular bypass. We describe three cases where there was vascular injury during surgery which were managed by direct repair. This implies the necessity of learning microvascular techniques for safely perform the surgery and save the patient from neurological deficits. Bang. J Neurosurgery 2023; 12(2): 122-124